Internalization of multicultural education in improving students' multicultural competence - Mardhiah Mardhiah; Dafid Ginting; Titi Mumfangati; Meisuri Meisuri; Endang Fatmawati; Misbahul Jannah; Siyono Siyono; Muhammad Haris; Nanda Saputra (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: This article aims to describe multicultural education in improving students' multicultural competence. It is very important to teach multicultural values in the school environment to help students understand the importance of mutual respect. Multicultural education is very significant for its application in Indonesia, in the midst of racial, religious, cultural, and customs diversity. MATERIALS AND METHODS: This study uses a qualitative research approach with the Meta-Synthesis method to map research results from several kinds of literatures. The number of articles studied in this research was 27 articles. School is the most effective place in developing students' multicultural competence; therefore, schools must implement learning that prioritizes multicultural principles without discriminating against cultural, racial, linguistic, and cultural backgrounds of students. RESULT: The results of this study indicate that 1). The concept of multicultural education applied in schools is able to increase students' multicultural competence and 2). Students are more open to dealing with existing differences. As for the results of research in an elementary school education environment which is the object of research, this is based on the importance of multicultural education being implemented from an early age. CONCLUSION: Multicultural education is very important to increase awareness and tolerance among students. By internalizing multicultural education, students can interpret differences as a matter of course and make students more open to others both in the school environment and in the community environment.